Is subclinical thyroid dysfunction in the elderly associated with depression or cognitive dysfunction? - Roberts, L; Pattison, H; Roalfe, A; Franklyn, J; Wilson, S; Hobbs, F; Parle, J (2006)
BACKGROUND: Widespread use of automated sensitive assays for thyroid hormones and thyroid-stimulating hormone (TSH) has increased identification of mild thyroid dysfunction, especially in elderly patients. The clinical significance of this dysfunction, however, remains uncertain, and associations with cognitive impairment, depression, and anxiety are unconfirmed. OBJECTIVE: To determine the association between mild thyroid dysfunction and cognition, depression, and anxiety in elderly persons. DESIGN: Cross-sectional study. Associations were explored through mixed-model analyses. SETTING: Primary care practices in central England. PATIENTS: 5865 patients 65 years of age or older with no known thyroid disease who were recruited from primary care registers. MEASUREMENTS: Serum TSH and free thyroxine (T4) were measured. Depression and anxiety were assessed by using the Hospital Anxiety and Depression Scale (HADS), and cognitive functioning was established by using the Middlesex Elderly Assessment of Mental State and the Folstein Mini-Mental State Examination. Comorbid conditions, medication use, and sociodemographic profiles were recorded. RESULTS: 295 patients met the criteria for subclinical thyroid dysfunction (127 were hyperthyroid, and 168 were hypothyroid). After confounding variables were controlled for, statistically significant associations were seen between anxiety (HADS score) and TSH level (P = 0.013) and between cognition and both TSH and free T4 levels. The magnitude of these associations lacked clinical relevance: A 50-mIU/L increase in the TSH level was associated with a 1-point reduction in the HADS anxiety score, and a 1-point increase in the Mini-Mental State Examination score was associated with an increase of 50 mIU/L in the TSH level or 25 pmol/L in the free T4 level. LIMITATIONS: Because of the low participation rate, low prevalence of subclinical thyroid dysfunction, and other unidentified recruitment biases, participants may not be representative of the elderly population. CONCLUSIONS: After the confounding effects of comorbid conditions and use of medication were controlled for, subclinical thyroid dysfunction was not associated with depression, anxiety, or cognition.